Pancasila as Grundnorm and Islamic Religious Education as Moral Foundation: Strengthening Constitutional Order through Islamic Sociological Jurisprudence Theory - Nazila Riskiya Putri; Nayla Damayanti; Meifta Dian Safitri; Ahmad Muhamad Mustin Nasoha (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
This study aims to examine the position of Pancasila as a grundnorm within the Indonesian constitutional system and the role of Islamic Religious Education as an ethical foundation in strengthening constitutional principles from the perspective of Islamic sociological legal theory. The methodology employed is a qualitative approach using library research, involving the analysis of various relevant literature sources. The findings indicate that Pancasila plays a fundamental role in the Indonesian legal system, serving as the highest norm in the hierarchy of laws, while also functioning as an ethical guideline in the life of the nation and the state. Islamic Religious Education plays a significant role in shaping the moral constitution through the understanding of values such as honesty, justice, responsibility, and trustworthiness, in line with the principles of Pancasila. The integration of Pancasila values and Islamic teachings, viewed through the lens of sociological law, demonstrates that effective law is not merely normative but also responsive to social realities. Therefore, Islamic sociological legal theory can strengthen the Indonesian constitutional system through the integration of normative, moral, and sociological values, resulting in a more responsive, just, and contextually relevant legal system.